Epithelioid angiosarcoma revealed by livedoid distal vascular emboli - Annika Fournier, MD; Sébastien Humbert, MD; Olivier Morel, MD; Marcela-Ionela Mihai, MD; Charles-Henri Bretagne, MD; Marie-Paule Algros, MD; Séverine Valmary-Degano, MD (Elsevier, 2018)
Angiosarcomas are rare malignant mesenchymal tumours with endothelial differentiation, which may arise in any organ. Angiosarcoma of the aorta is even more exceptional. It can be complicated by distal embolization, resulting in suggestive clinical pictures such as cyanotic skin lesions of the extremities or livedo reticularis. We report a case of an epithelioid angiosarcoma revealed by bone metastasis and which caused cutaneous intravascular emboli prior to diagnosis. Intravascular distal embolization arising from a primary malignant vascular tumour of the aorta is extremely rare and this diagnosis can be a challenge for the pathologist, in particular without the clinical context. Keywords: Epithelioid angiosarcoma, Metastatic angiosarcoma, Cutaneous embolization, Livedo reticularis, Stent prosthesis